Neogene to Present paleostress field in Eastern Iran (Sistan belt) and implications for regional geodynamics. Issue 2 (23rd February 2017) - Jentzer, Michael; Fournier, Marc; Agard, Philippe; Omrani, Jafar; Khatib, Mohammad Mahdi; Whitechurch, Hubert
Abstract: We conducted a stress field analysis of the northern part of the ~700 km long north‐south trending, seismically active Sistan orogenic belt of Eastern Iran formed as a result of the closure of a branch of the Neo‐Tethys during the early Cenozoic. Fault kinematic data reveal drastic changes in the stress regime of Eastern Iran during the late Cenozoic, with three successive directions of compression ( σ 1 ), from 90°N during the middle‐ late Miocene to 60°N during the late Pliocene and 25°N during the Plio‐Quaternary, thereby evidencing a counterclockwise rotation of about 65° of σ 1 in less than 10 Myr. As shown by compilation of paleostress data, Plio‐Quaternary direction of compression in Sistan coincides with the one recorded across the whole of Iran and with present‐day Arabia‐Eurasia convergence direction. This result suggests effective stress transfer from the Zagros collision and that Sistan is at present mechanically coupled and shortened along with the rest of the Iranian crust/lithosphere. By contrast, Miocene compression is markedly different in the Iranian hinterland (e.g., Sistan, Central Iran, and Kopet Dagh) and in the Zagros orogen. This could tentatively be related to the end of Sistan collision and/or to the imprint of active deformation occurring further to the east. The intermediate late Pliocene compression (i.e., 60°N) could correspond to the progressive reorientation of the stress regime, as Sistan gets mechanically coupled to the Zagros collision. Key Points: Stress evolution in the Sistan (Eastern Iran) during the Neogene Stress transfer throughout Iran during the Neogene Zagros collision and stress sources in Iran during the Neogene